Synthesis and Characterization of Open-ring Complexes Formed in the Reaction of Lanthanides(III) with Salicylaldehyde Schiff base Containing Pyridine and Amide Bridge - Lihua, Cai; Peizhi, Hu; Xiaolan, Du; Bo, Zheng; Xiaocong, Zhuang (Asian Journal of Chemistry, 2016)
Eleven new lanthanide(III) complexes have been prepared by the reaction lanthanide chlorides and the salicylaldehye Schiff base ligand (L) in ethanol solution. They have been characterized by elemental analysis, molar conductivity data, IR, UV and 1H NMR. The measured results shows that lanthanide(III) is coordinated with the Schiff base by ratio of 1:1. The formula of the complexes is [LnLH2O]Cl3, where Ln = La, Nd, Sm, Eu, Gd, Dy, Ho, Er, Tm, Yb and Lu.